2022
DOI: 10.1038/s41598-022-05542-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of charge-balanced transcutaneous electrical nerve stimulation on rodent facial nerve regeneration

Abstract: This study aimed to investigate the effect of charge-balanced transcutaneous electrical nerve stimulation (cb-TENS) in accelerating recovery of the facial function and nerve regeneration after facial nerve (FN) section in a rat model. The main trunk of the left FN was divided and immediately sutured just distal to the stylomastoid foramen in 66 Sprague–Dawley rats. The control group had no electrical stimulus. The other two groups received cb-TENS at 20 Hz (20 Hz group) or 40 Hz (40 Hz group). Cb-TENS was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Studies of electrical stimulation with a 20-Hz frequency on the damaged facial and sciatic nerves of rats demonstrated increased BDNF expression and improved nerve structure. 50 52 Compared to the control group, sciatic function index and axonal density were increased by 26% and 19%, respectively, after 3 weeks of 20-Hz electrical stimulation. 52 Facial function recovered more rapidly in the 20- and 40-Hz electrical stimulation groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies of electrical stimulation with a 20-Hz frequency on the damaged facial and sciatic nerves of rats demonstrated increased BDNF expression and improved nerve structure. 50 52 Compared to the control group, sciatic function index and axonal density were increased by 26% and 19%, respectively, after 3 weeks of 20-Hz electrical stimulation. 52 Facial function recovered more rapidly in the 20- and 40-Hz electrical stimulation groups.…”
Section: Discussionmentioning
confidence: 89%
“… 52 Facial function recovered more rapidly in the 20- and 40-Hz electrical stimulation groups. 50 As for the muscle action potentials, the regenerated sciatic nerves treated with 2-Hz of electrical stimulation had a significantly shorter latency, longer duration, and faster nerve conductive velocity compared to the other groups (the control, 1-Hz, 20-Hz, and 200-Hz groups). 31 A 2-Hz burst pulse showed better nerve regeneration capacity than 100-Hz pulse electrical stimulation in the study by Cavalcante Miranda de Assis et al, 47 and NGF expression was maximized (4.1-fold increase) with 1-Hz electrical stimulation on cultured Schwann cells in the study by Huang et al 48 Morimoto et al reported the neuroprotective effect of 1-, 5-, and 20-Hz electrical stimulations observed from retinal ganglion cells and suggested that other parameters, such as current intensity, pulse duration, and stimulation time, have potential for different neuroprotective effects.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Transcutaneous ES system, comprised of an extracorporeal programmable power generator (generally supply adjustable low-frequency pulse current), transcutaneous output leads, and electro-acupuncture or implanted metal-sheet electrodes has been extensively studied for the clinic treatment of PNI. [121][122][123] In that scenario, trained operators can formulate custom-tailored ES courses dependent on different patients thus achieving scheduled modulating. Exerted pulsed current incurs the change of either sides of the membrane potential difference (depolarization, positive charges on the excitable cell membrane surface are captured by the negative charges on the electrode) and consequently opening the voltage-gated calcium channels, thus allowing extracellular Ca 2+ cell physiological activity and function.…”
Section: Transcutaneous Es Systemmentioning
confidence: 99%
“…14 In particular, our group found that charge-balanced transcutaneous electrical nerve stimulation (cb-TENS) using a 20 Hz pulse waveform was very effective in regenerating the FN. 15 Therefore, when the FN is unavoidably resected and direct anastomosis is impossible, using cb-TENS may be more efficient than using PLCL conduits alone. If this is proven, it has important implications not only for the FN but also for treating other damaged nerves in vivo.…”
Section: Introductionmentioning
confidence: 99%